The Impact of Organizational Commitment and Motivation on Turnover Intention with Job Satisfaction Asus a Variable Intervening at PT Bgr Logistics Indonesia Post-Merger - Alib Sabarrudin, Muhammad; Masydzulhak Djamil (Dinasti International Journal of Digital Business Management, 2023)
This study's objective was to investigate the connection between commitment organizations, and motivation and turnover intention at PT BGR Logistik Indonesia using job satisfaction as an intervening variable. There are 896 individuals living there in total. Using a random sampling technique, 277 persons were included in the sample. The research method in this study uses a quantitative approach and data analysis uses SMART-PLS. The research results prove that (1) organizational commitment has a negative and significant effect on turnover intention. (2) Job satisfaction has a negative and significant effect on turnover intention (3) Motivation has a not positive and significant impact on Turnover Intention (4) Organizational commitment has a positive and significant effect on job satisfaction (5) Motivation has a positive and significant effect on job (6) Job satisfaction has a negative and significant impact on the intention to leave the organization. (7) Motivation, acting as an intervening variable, has a detrimental and considerable impact on the desire to leave. Suggestions and input for PT. BGR Logistik Indonesia pays more attention to organizational commitment and work motivation.